In case, it is 2x-6x²+8x, Isolating all terms on the left side:
1) (2x-6x²+8x) =(2x +2)
2x-6x²+8x -2x -2 =0
-6x²+8x -2 =0
6x² -8x -2 =0
![\begin{gathered} x=\frac{8\pm\sqrt[]{64-4(6)(-2)}}{12} \\ \\ x_1=\frac{2+\sqrt[]{7}}{3} \\ x_2=\frac{2-\sqrt[]{7}}{3}_{} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ulq3knrd4cr7oegy24wsy7x9sh10jdvon0.png)
2) In case, it is 2x²-6x²+8x. Isolating all terms on the left side.
2x²-6x²+8x =2x +2
-4x²+8x-2x -2=0
-4x² +6x -2 =0
4x²-6x+2=0
![\begin{gathered} x=\frac{6\pm\sqrt[]{(36)-4(4)(2)}}{8} \\ \\ x_1=1 \\ \\ x_2=(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d8to67fee175vj8feh2o5rfr8iibwm36et.png)